From hypoxic pockets to daily routines: linking brain oxygenation and cognitive resilience - Jiao, Dian (Frontiers in Aging Neuroscience, 2025)
The discovery of hypoxic pockets within the cortical regions has transformed the understanding of cerebral oxygen dynamics, revealing their dual role as both contributors to neuronal adaptation and potential precursors to dysfunction. These transient oxygen-deprived microenvironments play a pivotal role in neurovascular coupling, synaptic plasticity, and angiogenesis, processes crucial for maintaining cognitive resilience and neuronal health. Investigating hypoxic pockets within cortical regions is particularly relevant in aging populations and individuals with neurodegenerative conditions. Concurrently, research underscores the ability of physical, social, and cognitive activities to modulate brain oxygenation, offering natural, accessible interventions to optimize oxygen delivery and utilization. This study synthesizes findings from neuroimaging, behavioral science, and longitudinal studies, illustrating how daily routines can mitigate hypoxia-induced cognitive decline and promote resilience. By integrating insights from centenarians, hypoxia-adapted species, and multimodal intervention studies, this framework highlights the transformative potential of lifestyle-based strategies in addressing cerebral oxygen deficits. The findings advocate for an interdisciplinary approach to develop targeted interventions for public health, rehabilitation, and personalized cognitive care.